The impact of common clients on employee mobility and organizational growth. Issue 2 (11th June 2021) - Kim, Yeongsu (Anthony)
Abstract: This article examines how client overlap (i.e., common clients) between a sourcing (leaving) and a destination (hiring) firm influences employee mobility and how it subsequently restricts growth in a firm. The central argument of this article is that, since client overlap encourages individual mobility decisions, and hiring firms solicit employees from client-overlapping competitors, there will be more employee mobility between firms that have more clients in common. Furthermore, I suggest that losing employees to a client-overlapping competitor can potentially restrict the sourcing firm's growth, but such a negative effect can be mitigated through the firm's leverage ratio. By examining the employee mobility of US-based law firms, this study finds that client overlap facilitates employee mobility. Furthermore, this study also finds that a loss of human capital to a client-overlapping competitor restricts the growth of the sourcing firm. However, such a negative association can be mitigated by the internal allocation of human capital (i.e. leverage ratio).